O uso da Tecnologia da Informação enquanto contribuição para o trabalho arquivístico: um estudo de caso da implementação do sei na Universidade Federal do Amazonas - Alves, Anne Caroline Ferreira (Brasil, 2024)
Archival Science is of great importance in storing, organizing, and maintaining documents that were and are necessary for the construction of society and the processes of various institutions. It is necessary to know the many changes that have occurred over the years with Archival Science, the improvements in the processes, and understand what the particularities of a document are, since it is present in virtually every sphere, whether social, political, economic, religious, or educational, all will make use and need to resort to the archives. Therefore, it is necessary to know the technological tools that have been making this process, years ago, time- consuming, and exhaustive, now faster and more efficient. With the implementation of the SEI, the whole documental process was made easier, and because of this, it is a system that has been implanted all over Brazil, since its quality. This research analyzed the term Archival Science, in addition to making a comparison with information technology, and observed how the implementation of the SEI has facilitated this entire documentary process, through an interview about the system’s arrival at UFAM.